Mechanical properties and hermal properties of PMMA/EVA/KENAF short fiber composites prepared by twin screw extruder and injection holding - Hajida-oh, Lukman (School of Materials Engineering, Universiti Malaysia Perlis, 2012)
The influence of injection temperature on mechanical properties (tensile test) of PMMA/EVA/kenaf short fibre composites by using injection molding was investigated. Besides that, the effect of EVA on mechanical properties (tensile test, impact test and fracture observation), thermal properties (DSC test, TGA test) and dynamic mechanical analysis of PMMA also important to carried out at different ratio of PMMA/EVA. At last, the effect of kenaf short fibre on the mechanical properties (tensile test, impact test and fracture observation), thermal properties (TGA test) and dynamic mechanical analysis of PMMA/EVA/kenaf short fibre composites was studied.